Investigation of Lamproglena pulchella (Nordmann, 1832) on Capoeta trutta and Chondrostoma regium caught in Keban Dam Lake (Elazig, turkey) - Saglam, N (Blackwell Wissenschafts-Verlag Gmbh, 1998)
In this study the eyes, gills, skin, fins and mouths of 216 individuals of two cyprinids species (Capoeta trutta and Chondrostoma regium) caught in the Keban Dam Lake, Elazig, Turkey, were examined for the Lamproglena pulchella parasite; 135 L, pulchella were found on gills of 61 of 216 fish. Body sizes of some of the parasites were measured; prevalence. mean intensity and abundance of L. pulchella were 28.24, 2.21 +/- 2.17 and 0.63 +/- 1.52, respectively. No influence of host sex on parasite dispersion was observed.